2013
DOI: 10.1095/biolreprod.112.106195
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologies, Immunolocalization, and a Glycan Binding Screen Provide Insights into Plasmodium falciparum Interactions with the Human Placenta

Abstract: During pregnancy, Plasmodium falciparum-infected erythrocytes cytoadhere to the placenta. Infection is likely initiated at two sites where placental trophoblasts contact maternal blood: 1) via syncytiotrophoblast (STB), a multicellular transporting and biosynthetic layer that forms the surface of chorionic villi and lines the intervillous space, and 2) through invasive cytotrophoblasts, which line uterine vessels that divert blood to the placenta. Here, we investigated mechanisms of infected erythrocyte seques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 76 publications
2
22
0
1
Order By: Relevance
“…CSA is thought to be a component of the proteoglycan matrix present in the intervillous space and (moderately) on the syncytiotrophoblast cell layer of the human placenta, [2][3][4][5] although one study has suggested that placental CSA is of fetal origin and is in contact with maternal blood only in the advanced and chronically infected placenta after syncytiotrophoblast denudation. 6 According to this latter study, initial steps of placental cytoadhesion might involve Lewis antigens and other sialic acid-containing carbohydrates present on the intact syncytium and on endovascular invasive cytotrophoblasts. 6 Sequestration of parasitized erythrocytes in the placenta can give rise to maternal malaria, a severe syndrome associated with low birth weight, prematurity, and chronic intervillositis.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…CSA is thought to be a component of the proteoglycan matrix present in the intervillous space and (moderately) on the syncytiotrophoblast cell layer of the human placenta, [2][3][4][5] although one study has suggested that placental CSA is of fetal origin and is in contact with maternal blood only in the advanced and chronically infected placenta after syncytiotrophoblast denudation. 6 According to this latter study, initial steps of placental cytoadhesion might involve Lewis antigens and other sialic acid-containing carbohydrates present on the intact syncytium and on endovascular invasive cytotrophoblasts. 6 Sequestration of parasitized erythrocytes in the placenta can give rise to maternal malaria, a severe syndrome associated with low birth weight, prematurity, and chronic intervillositis.…”
Section: Introductionmentioning
confidence: 94%
“…6 According to this latter study, initial steps of placental cytoadhesion might involve Lewis antigens and other sialic acid-containing carbohydrates present on the intact syncytium and on endovascular invasive cytotrophoblasts. 6 Sequestration of parasitized erythrocytes in the placenta can give rise to maternal malaria, a severe syndrome associated with low birth weight, prematurity, and chronic intervillositis. PfEMP1 is presented in knoblike protrusions that anchor PfEMP1 to the erythrocyte membrane skeleton.…”
Section: Introductionmentioning
confidence: 94%
“…Measures can be taken to artificially extend multivalency of soluble proteins and thereby improve glycan array sensitivity as discussed in Section 4.2. In addition to soluble proteins, whole viruses, bacteria, yeasts, or mammalian cells can be screened (18,61,62).…”
Section: Incubation and Readoutmentioning
confidence: 99%
“…The interaction between red blood cells infected with Plasmodium falciparum and sialosides with a potential role in placental malaria was shown with a whole cell-binding assay (61). An interesting whole cell-binding approach was used to study the specificity of the ligand-binding domains of Epa1, Epa6, and Epa7 of the pathogenic yeast Candida glabrata: The adhesins were recombinantly expressed on the surface of Saccharomyces cerevisiae (62).…”
Section: Microbial and Viral Adhesinsmentioning
confidence: 99%
“…For example, in pregnancy-associated malaria, the VAR2CSA variant of PfEMP1 binds placental CSA located in the villous stromal cores of the placenta, which become exposed to maternal blood upon denudation of syncytiotrophoblasts. 5,6 For years, investigators have speculated that other PfEMP1 variants will prove to bind receptors that are preferentially expressed in one or another vascular bed, such as those of the brain, lung, kidney, or bone marrow (Figure 1). In the next section, we discuss one such receptor, namely the endothelial protein C receptor (EPCR), whose relatively low expression levels and nonredundant functionality in the brain provide clues toward understanding the focal manifestations of CM.…”
Section: Malaria and Vascular Diversitymentioning
confidence: 99%